Effect of docetaxel added to bicalutamide in Hormone-Naive non-metastatic prostate cancer with rising PSA, a randomized clinical trial (SPCG-14) - Josefsson Andreas; Jellvert Åsa; Holmberg Erik; Brasso Klaus; Petersen Peter Meidahl; Aaltomaa Sirpa; Luukkaa Marjaana; Verhagen Paul; de Wit Ronald; Ahlgren Göran; Andren Ove; Castellanos Enrique; et al. (Taylor & Francis Ltd, 2025)
BackgroundHistorically, endocrine therapy was used in a range of scenarios in patients with rising PSA, both as a treatment for locally advanced non-metastatic prostate cancer and PSA recurrence following curative intended therapy. In the present study the objective was to investigate if chemotherapy added to endocrine therapy could improve progression-free survival (PFS).Materials and MethodsPatients with hormone-naive, non-metastatic prostate cancer and rising prostate-specific antigen (PSA), enrolled from Sweden, Denmark, the Netherlands, and Finland, were randomized to long-term bicalutamide (150 mg daily) or plus docetaxel (75 mg/m(2), q3w, 8-10 cycles) without prednisone, after stratification for the site, prior local therapy or not, and PSA doubling time. The primary endpoint was 5-year PFS analyzed with a stratified Cox proportional hazards regression model on intention to treat basis.ResultsBetween 2009 and 2018, a total of 348 patients were randomized; 315 patients had PSA relapse after radical treatment, 33 patients had no prior local therapy. Median follow-up was 4.9 years (IQR 4.0-5.1). Adding docetaxel improved PFS (HR 0.68, 95% CI 0.50-0.93; p = 0.015). Docetaxel showed an advantage for patients with PSA relapse after prior local therapy (HR 0.67, 95% CI 0.49-0.94; p = 0.019). One event of neutropenic infection/fever occurred in 27% of the patients receiving docetaxel. Limitations were slow recruitment, lack of enrolling patients without radical local treatment, and too short follow-up for evaluation of overall survival in patients with PSA relapse.ConclusionDocetaxel improved PFS in patients starting bicalutamide due to PSA relapse after local therapy or localized disease without local therapy. Confirmatory studies of the efficacy of docetaxel in the setting of PSA-only relapse in addition to endocrine therapies may be justified if longer follow-up will show increased metastatic-free survival.